PENGARUH TEMPERATUR UAP TERHADAP EKSPANSI VOLUME DAN TEGANGAN TERMAL RODA LORI DISTASIUN PEREBUSAN PT. X - Herry Darmadi; Jery Manaor Simarmata; Sorta Lumbantoruan; Nurlianna Tarigan; Dian Kurnia; Novia Nelza (Jurnal Mekanova : Mekanikal, Inovasi dan Teknologi, 2026)
Lorry wheels at the boiling station of a Palm Oil Mill (PKS) are exposed to high-temperature saturated steam during the boiling process, which causes volume expansion and thermal stress in the wheel material. This study aims to analyze the effect of steam temperature on volume expansion and thermal stress on lorry wheels in the palm oil mill sterilization station. Data were obtained through direct observation and theoretical calculations using ASTM A36 steel material parameters. The results show that an increase in steam temperature from 110.27°C to 133.59°C causes volume expansion of up to 1.39 × 10⁻⁵ m³ and thermal stress of up to 241.41 MPa, approaching the material's yield strength (250 MPa). It is concluded that steam temperature significantly affects deformation and potential failure of lorry wheel material.